IMMATURE GRANULOCYTE PERCENTAGE –A PREDICTOR OF INFECTIONS IN PATIENTS IN INTENSIVE CARE UNIT SETTING - Hyder, Ali; Uddin, Nasir; Mahmood, Asad; Mahmood, Rafia; Iqbal, Muhammad Ijaz (Pakistan Armed Forces Medical Journal, 2020)
Objective: To determine diagnostic importance of immature granulocyte percentage in patients with infection in early stages in hospital settings. Study Design: Cross sectional study. Place and Duration of Study: Department of Haematology, Armed Forces Institute of Pathology (AFIP) Rawalpindi, from Oct 2017 to Oct 2018. Methodology: One hundred patients were inducted who fulfilled the criteria of systemic inflammatory response syndrome (SIRS) and sepsis. Four ml blood from the patients was taken via venepuncture or indwelling catheter in an EDTA tube, White blood cell count (WBC) and immature granulocyte (IG) percentage was analyzed by using Sysmex XN3000 haematology analyzer. Results: The diagnostic accuracy of immature granulocyte percentage in patients with sepsis as compared to white blood cell count was recorded as 67.40%, 82.35%, 94%, 70% and 87.14% for sensitivity, specificity, positive predictive value, negative predictive value and accuracy rate respectively. Conclusion: Immature granulocyte count at 1.0% is a reliable and effective predictor of infection, validating its addition into the diagnostic protocols in the intensive care unit settings